The Effect of Cultural Heterogeneity and Economic Uncertainty on Cash Holdings - Felicia Julianti; Sung Suk Kim (Budapest International Research and Critics University, 2022)
The objective of this study is to decide the effect of social variety and monetary vulnerability on cash property in 22 developing business sector nations. We check three significant discoveries out. First off, corporate money property are unfavorably connected with individualism and decidedly connected with uncertainty avoidance. Second, corporate money property are connected with economic uncertainty. We likewise investigate the aggregation and scattering of money property by analyzing the connection between business size, productivity, research and development, net working capital, and market to book, which are all well related while influence is unfavorably related.